Effectiveness of Natural PGR Made from Shallot Filtrate and Aloe vera on the Growth of Cayenne Pepper (Capsicum frutescens L.) - Irmadhani, Dwi; Dewi, Sari Kusuma (LenteraBio : Berkala Ilmiah Biologi, 2025)
Cayenne pepper (Capsicum frutescens L.) is popular cooking fruit because the majority likes spicy flavor. Sometimes, there is a surge in prices because a decrease in production that occurs due to several factors, one of which is during the planting and cultivation process. Farmers overcome these problems using natural Plant Growth Regulators (PGR) from shallot filtrate and Aloe vera as growth support. The auxin and gibberellin hormones contained in these materials can be used to support the growth of cayenne pepper. This study aims to determine the effect of natural PGR administration and the most optimal concentration of natural PGR from these materials on the growth of cayenne pepper. This study used Randomized Block Design one factorial, namely the concentration of natural PGR with 5 concentrations control, 60%, 70%, 80%, and 90% with five repetitions. The parameters measured were plant height, number of leaves, and stem diameter. Data analysis used One-Way ANOVA test, followed by Duncan's test if significant. The results showed there was an effect of natural PGR, and 90% were the concentrations that provided the best growth with the highest average value of plants 12 cm, the largest number of leaves 10.8 strands, and the largest stem diameter value 1.76 mm.